Comparison between intermediate and severe coronary stenoses and clinical outcomes of an OCT-guided PCI strategy. Issue 5 (May 2016) - Di Vito, Luca; Cattabiani, Maria Alberta; Paoletti, Giulia; Yoon, Joo Heung; Chisari, Alberto; Gramegna, Mario; Versaci, Francesco; Castriota, Fausto; Prati, Francesco
Abstract : Aims: We compared optical coherence tomography (OCT) features of intermediate and severe coronary stenoses in patients with stable angina and acute coronary syndrome (ACS), and tested the clinical impact of an OCT-based strategy for treating intermediate stenoses. Methods: The study enrolled 135 consecutive patients with either ACS or stable angina and a single de-novo coronary stenosis. Patients were divided into two groups: intermediate stenosis defined as quantitative coronary angiography percentage narrowing less than 70%, or presence of angiographic vessel haziness and severe stenosis with percentage narrowing more than 70%. OCT was performed to assess features of plaque vulnerability and to measure the minimal lumen area. We also appraised the 12-month rate of major adverse event (MACE) of an OCT-guided strategy of percutaneous coronary intervention (PCI) based on the presence of thrombus and/or minimal lumen area less than 3.0 mm 2 . Results: Fifty-six patients had intermediate stenoses, whilst 79 had severe stenoses. In the 'intermediate stenosis group', patients with stable angina had a lower asymmetric index ( P = 0.02) and a greater calcific arc ( P = 0.0001). In the 'severe stenosis group', intermediate lesions of patients with ACS exhibited a greater lipid arc as compared with patients with stable angina ( P = 0.03). A higher prevalence of thin cap fibroatheroma was seen in patients with ACS of both groups. The incidence of MACE was not significantly different between patients with an intermediate stenosis who received PCI vs. optimal medical therapy on the basis of OCT findings ( P = 0.26). Conclusions: Intermediate coronary stenoses showed distinctive OCT-based features according to the initial clinical presentation. The adoption of an OCT-guided PCI strategy, based on the presence of coronary thrombus and significant vessel narrowing, led to encouraging results.